Attitude, Anxiety, Psychological Effects and Prevention during COVID-19 in India - Singh, Debabrata; Prusty, Shakti Ketan; Sarangi, Suman Sekhar; Sahoo, Surjeet; Biswal, Anil Kumar (Indian Journal of Pharmaceutical Education and Research, 2020)
With previous health warnings, personal anxieties could feed behavioral changes with many people of India considering notable changes in their transportation use and anticipating in preparation the purchase of goods, particularly masks. Asian respondents were especially likely to have talked about the pandemic with friends, whereas onefourth of respondents globally had talked about the pandemic with their family. Our data on the correlation indicates that these conversations may increase existing rates of anxiety. Practitioners need to be mindful that rumors spread rapidly during periods of pandemic danger, with significant risks of both emotional and physical ‘contagion’ amongst individuals. Any rise in anxiety may lead to sudden changes in behavior, which can quickly lead to shortages and can enhance the need for treatment at home.
Keywords: COVID-19; Psychology; Attitude; Lockdown; Anxiety; Quarantine